Scapulothoracic fusion with endobutton system for an isolated traumatic serratus anterior paralysis - Raif Özden (Dicle Medical Journal, 2013)
Scapular winging is a relatively rare disorder than the othershoulder diseases. Scapulothoracic fixation has beenshown to be effective in relieving pain, improving cosmetics,and restoring function. The most common cause isparalysis of the serratus anterior muscle. Paralysis ofthe serratus anterior muscle may result from a variety ofcauses. Sixteen year old male patient developed wingingof the scapula after long thoracic nerve injury (serratus anteriormuscle paralysis) following a blunt trauma. Scapulothoracicfixation was considered in order to relieve thepatient’s complaints. Stabilization of the scapulothoracicjoint was performed using an undescribed method withthe use of a endobutton system (Smith &Nephew). Aftera six-month follow up the patient’s complaint of pain disappeared,shoulder imbalance was restored with an improvementin shoulder abduction and in flexion.Key words: Scapular winging, long thoracic nerve injury,scapulothoracic fixation